Convair Report to Supervision, Number 1040, March 22, 1979 - Adams, Richard E. (General Dynamics Corporation. Fort Worth Division., 1979)
Newsletter written for supervisors working at the Convair Division in Fort Worth containing news about events and activities, workplace reminders, and other relevant information.